PERAMALAN LAJU INFLASI, SUKU BUNGA INDONESIA DAN INDEKS HARGA SAHAM GABUNGAN MENGGUNAKAN METODE VECTOR AUTOREGRESSIVE (VAR) - Priska Rialita Hardani; Abdul Hoyyi; Sudarno Sudarno (Jurnal Gaussian, 2017)
Inflation, Bi Rate (SBI) and the composite stock price index (IHSG) is an economic instrument and often seen as divorce progression of the economic progress of a country. Inflation, Bi Rate and IHSG is a multivariate time series that show activity for a certain period. One method to analyze multivariate time series is Vector Autoregressive (VAR). VAR method is a simultaneous equation model has several endogeneous variables. This research uses secondary data of inflation, SBI and IHSG on period January to June 2016. The VAR model acquired is a model VAR(4), with parameters estimated using the Ordinary Least Square (OLS). The selection model VAR(4) is based on the smallest value of AIC 4,255482 with value of MAPE is 47,11%. Keywords:  Inflation, SBI, IHSG, Time Series Multivariate, Forecasting, Vector Autoregressive (VAR).